Perkembangan Matematika dan Pendidikan Matematika Di Indonesia - jonathan simanjuntak (Sepren, 2021)
This study aims to determine the development of mathematics education in Indonesia. The research method used is descriptive method, by presenting a description, clarification of a phenomenon and facts in mathematics. As well as library research (library research). By collecting several books, articles and opinions from experts regarding the development of mathematics and mathematics education which are then developed with various existing findings. The results showed that the development of mathematics was based on philosophy, because philosophy is the root of all human knowledge, both scientific knowledge and non-scientific knowledge. The historical development of mathematics, Babiliona mathematics refers to all mathematics developed by the Mesopotamians since the beginning of Hellenism. At that time the development of mathematics expanded to several countries such as Egypt, Greece, Arabia and India. The development of Mathematics Education in Indonesia is never separated from the history of the curriculum. The importance of mathematics in life is not surprising if mathematics learning has developed and adapted to the needs of the times. The development of mathematics learning in Indonesia is as traditional mathematics, modern mathematics, and modern mathematics.